Potential UV-Protective Effect of Freestanding Biodegradable Nanosheet-Based Sunscreen Preparations in XPA-Deficient Mice - Tomomi Hatanaka; Khampeeraphan Ramphai; Shun Takimoto; Hiromi Kanda; Nami Motosugi; Minoru Kimura; Tomotaka Mabuchi; Midori Oyama; Tomoharu Takeuchi; Yosuke Okamura (MDPI AG, 2022)
Xeroderma pigmentosum (XP) is a rare autosomal recessive hereditary disorder. As patients with XP are deficient in nucleotide excision repair, they show severe photosensitivity symptoms. Although skin protection from ultraviolet (UV) radiation is essential to improve the life expectancy of such patients, the optimal protective effect is not achieved even with sunscreen application, owing to the low usability of the preparations. Nanosheets are two-dimensional nanostructures with a thickness in the nanometer range. The extremely large aspect ratios of the nanosheets result in high transparency, flexibility, and adhesiveness. Moreover, their high moisture permeability enables their application to any area of the skin for a long time. We fabricated preparations containing avobenzone (BMDBM) based on freestanding poly (L-lactic acid) (PLLA) nanosheets through a spin-coating process. Although monolayered PLLA nanosheets did not contain enough BMDBM to protect against UV radiation, the layered nanosheets, consisting of five discrete BMDBM nanosheets, showed high UV absorbance without lowering the adhesive strength against skin. Inflammatory reactions in XPA-deficient mice after UV radiation were completely suppressed by the application of BMDBM-layered nanosheets to the skin. Thus, the BMDBM layered nanosheet could serve as a potential sunscreen preparation to improve the quality of life of patients with XP.